Transfusion Reactions in Pediatric Cancer Patients - Cakra Jati Pranata; Nur Suryawan; Delita Prihatni (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Transfusion is an essential component of supportive management for cancer patients with anemia and thrombocytopenia. It is generally safe; however, it has several risks and complications including those caused by transfusion reactions. This study aimed to describe transfusion reactions in pediatric cancer patients in a tertiary hospital in Indonesia. Methods: This was a descriptive cross-sectional study with a total sampling method. A prospective analysis was performed on episodes of blood transfusion in pediatric patients aged younger than 18 years old with cancer and were hospitalized at the Department of Child Health of the hospital from July to August 2019. After the consent of the parents, the patients were interviewed for various transfusion reactions. Data collected were presented using tables and charts.Results: Leukemia was the most frequent cancer in children cancer patients who need transfusion. Out of 42 children included, 155 episodes of transfusion were observed with 22 episodes showed transfusion reactions (14.2%). The most frequent manifestations were pruritus (31.8%), followed by combination of pruritus and erythema (27.4%) and fever (13.6%). These reactions appeared mostly in 1 to 2 hours (27.2%), with most were mild reactions (59.1%).Conclusion: Transfusion reactions mostly occurred among pediatric patients with cancer in the acute phase with clinical manifestation of allergic reactions, predominantly mild. Early identification of these reactions would result in better treatment and prevention for recurrence of transfusion reactions.